TINJAUAN HUKUM ISLAM TERHADAP ARISAN BERAS: STUDI KASUS DI DESA JAYI KECAMATAN SUKAHAJI KABUPATEN MAJALENGKA - Mualim, Mualim; Hidayat, Yayat; Masfufah, Ulfah (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2021)
This research began with the implementation of the rice gathering, which is an arisan activity that is carried out in Jayi Village. This gathering is carried out 3 times a year and is carried out after the harvest takes place. In this arisan in terms of payment, the fee is determined which will get rice where the rice received will vary due to the uncertain price of rice. To answer this community phenomenon, the researchers formulated the problems that will be studied in this study, namely: 1) How is the implementation of the rice social gathering in Jayi Village, Sukahaji District, Majalengka Regency; 2) how is Islamic law reviewing the implementation of the rice social gathering in Jayi Village, Sukahaji District, District Majalengka. The research method used by the author is qualitative research, which merely describes the situation/events in the field (field research) in the form of observations, interviews and also documentation. The data that the writer obtained was then reduced, presented and concluded using descriptive analysis techniques. The results of this study concluded that the rice arisan in Jayi Village, Sukahaji District, Majalengka Regency, was in accordance with Islamic law and some were not in accordance with Islamic law. The terms of the debt and receivables (qarḍ) are in accordance with the provisions. Then in the payment of this rice arisan, the muamalah principles have been applied, because the arisan participants are at risk with each other with the determination of the arisan payment. However, in obtaining the arisan rice obtained by the arisan participants are different, so that the practice of this rice arisan contains elements of gharar and lack of justice.